PEPtalk2: results of a pilot randomised controlled trial to compare VZIG and aciclovir as postexposure prophylaxis (PEP) against chickenpox in children with cancer. Issue 1 (13th January 2019) - Bate, Jessica; Baker, Stephen; Breuer, Judith; Chisholm, Julia C; Gray, Juliet; Hambleton, Sophie; Houlton, Aimee; Jit, Mark; Lowis, Stephen; Makin, Guy; O'Sullivan, Catherine; Patel, Soonie R; et al.
Abstract : Objective: To determine the likely rate of patient randomisation and to facilitate sample size calculation for a full-scale phase III trial of varicella zoster immunoglobulin (VZIG) and aciclovir as postexposure prophylaxis against chickenpox in children with cancer. Design: Multicentre pilot randomised controlled trial of VZIG and oral aciclovir. Setting: England, UK. Patients: Children under 16 years of age with a diagnosis of cancer: currently or within 6 months of receiving cancer treatment and with negative varicella zoster virus (VZV) serostatus at diagnosis or within the last 3 months. Interventions: Study participants who have a significant VZV exposure were randomised to receive PEP in the form of VZIG or aciclovir after the exposure. Main outcome measures: Number of patients registered and randomised within 12 months of the trial opening to recruitment and incidence of breakthrough varicella. Results: The study opened in six sites over a 13-month period. 482 patients were screened for eligibility, 32 patients were registered and 3 patients were randomised following VZV exposure. All three were randomised to receive aciclovir and there were no cases of breakthrough varicella. Conclusions: Given the limited recruitment to the PEPtalk2 pilot, it is unlikely that the necessary sample size would be achievable using this strategy in a full-scale trial. The study identified factors that could be used to modify the design of a definitive trial but other options for defining the best means to protect such children against VZV should be explored. Trial registration number: ISRCTN48257441, EudraCT number: 2013-001332-22, sponsor: University of Birmingham.